INCREASING THE EFFICIENCY OF THE IMPLEMENTATION OF LOGISTICS SUPPORT MEASURES BY PROVIDING PRACTICAL RECOMMENDATIONS FOR IMPROVING THE PROCESSES OF MOVEMENT OF MATERIAL AND TECHNICAL ASSETS TO OBTAIN THE MAXIMUM EFFECT FROM AVAILABLE RESOURCES - Derevianko, Maksym; Nesterenko, Roman; Rikunov, Oleh (Honor and Law, 2023)
The success of the mission depends largely on timely, complete and uninterrupted logistics support. Timely, complete and uninterrupted logistics support at the current stage of development in the conditions of warfare requires constant study, analysis and improvement. The war of Ukraine with superior enemy forces forced the search for new forms and methods of logistics support in various combat conditions. The process of finding optimal solutions should be carried out at all levels from the Main Logistics Directorate "J-4", brigade ("О-4"), battalion ("S-4") to platoon, facility (position). The efficiency of the implementation of logistics support measures is influenced by a large number of various factors that must be taken into account when planning and organizing logistics support. The mission and purpose of logistics support are clearly defined and its implementation has a direct impact on the effectiveness of combat operations. But taking into account the tactics of the enemy, the logistics support of troops with road vehicles in the conditions of the active phase of combat operations has the corresponding risks regarding timely, complete and uninterrupted support of the troops. The paper substantiates the urgency of the problem of finding productive ways of logistics support of troops with road vehicles in the conditions of the active phase of combat operations. By means of the proposed methods, it is possible to increase the efficiency of logistics support at a military unit.